2021
DOI: 10.1371/journal.pntd.0009353
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsial infections: A blind spot in our view of neglected tropical diseases

Abstract: Rickettsial diseases are a group of vector-borne bacterial infections that cause acute febrile illness with potentially severe or fatal complications. These vector-borne diseases are prevalent in tropical and subtropical regions worldwide and disproportionately affect poorer communities but are scientifically underrecognized. Despite this, they are not included in the World Health Organization’s list of neglected tropical diseases nor were they mentioned in Peter Hotez’s recent reflections on “What constitutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…In addition to transovarial transmission of R. conorii in ticks, domestic dogs are competent reservoirs of R. conorii which can further raise pathogen prevalence in ticks [ 118 ]. Rickettsia conorii and other members of the SFG Rickettsia are overlooked human pathogens that can persist in human dominated landscapes and cause morbidity, mortality, and economic losses in marginalized populations [ 119 ]. Comprehensive surveillance of SFG Rickettsia in vectors, humans, and animals from endemic areas is needed to inform public health priorities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to transovarial transmission of R. conorii in ticks, domestic dogs are competent reservoirs of R. conorii which can further raise pathogen prevalence in ticks [ 118 ]. Rickettsia conorii and other members of the SFG Rickettsia are overlooked human pathogens that can persist in human dominated landscapes and cause morbidity, mortality, and economic losses in marginalized populations [ 119 ]. Comprehensive surveillance of SFG Rickettsia in vectors, humans, and animals from endemic areas is needed to inform public health priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The combined limitations of current serological and molecular diagnostics mean that diagnosis in the acute phase remains elusive, and empirical treatment is often given without any subsequent confirmation of diagnosis. The challenges in diagnosis perpetuate the neglected nature of rickettsial infections-without confirmation of cases, the true burden of disease is underestimated, leading to lack of development in diagnostics and ongoing under appreciation of clinical significance [ 14 ].…”
Section: Current Challenges In Diagnosismentioning
confidence: 99%
“…Rickettsial infections are an important cause of undifferentiated febrile illness in endemic settings but are frequently unrecognised [ 10 , 11 , 12 ]. Fever and seroprevalence studies have demonstrated a significant burden of rickettsial disease globally [ 13 ]; however, they remain a neglected disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rickettsial diseases are prevalent in tropical and subtropical regions of the world and disproportionately affect those living in poverty with limited access to modern health care [ 2 ]. For decades, rickettsial diseases have been an overlooked cause of morbidity, mortality, and economic losses in marginalized populations [ 3 ]. Despite the increasing awareness of the importance of rickettsial diseases, there remains a lack of information on the prevalence of rickettsiae in vector species across all infective life stages.…”
Section: Introductionmentioning
confidence: 99%